Managing human resources / Luis R Gomez-Mejia; David B Balkin; Robert L Cardy - Gomez-Mejia, Luis R.
This work prepares future managers with a business understanding of the need for human resource management skills. The 'non-functional' HR approach used in this text also makes human resources relevant to anyone who has to deal with HR issues, even those. who do not hold the title of manager